2021
DOI: 10.3389/fpubh.2021.599280
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of COVID-19 Pandemic in Nepal: A Lockdown Scenario Analysis

Abstract: The Government of Nepal issued a nationwide lockdown from 24 March to 21 July 2020, prohibiting domestic and international travels, closure of the border and non-essential services. There were only two confirmed cases from 610 Reverse Transcription Polymerase Chain Reaction (RT-PCR) tests and no fatalities when the government introduced nationwide lockdown. This study aimed to explore the overall scenario of COVID-19 including spatial distribution of cases; government efforts, and impact on public health, soci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 29 publications
4
47
2
Order By: Relevance
“…The study conducted in China illustrated higher SARS-CoV-2 infection in males, 63.8% rather than in females, 36.2% which is in correspondence with our study analysis which demonstrated 68.7% and 31.3% male and female infection rate, respectively [ 7 ]. Our study also demonstrated the more infected age group, 20–29 years followed by age group 30–39 years, corresponding with the results obtained from the study conducted by Sharma et al illustrating males of age group 21–30 years to be more infected [ 22 ]. In contrast, one study reported a higher incidence rate among females [ 23 ], whereas some studies suggest higher infection in the age group 30–39 years followed by 20–29 years of age [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…The study conducted in China illustrated higher SARS-CoV-2 infection in males, 63.8% rather than in females, 36.2% which is in correspondence with our study analysis which demonstrated 68.7% and 31.3% male and female infection rate, respectively [ 7 ]. Our study also demonstrated the more infected age group, 20–29 years followed by age group 30–39 years, corresponding with the results obtained from the study conducted by Sharma et al illustrating males of age group 21–30 years to be more infected [ 22 ]. In contrast, one study reported a higher incidence rate among females [ 23 ], whereas some studies suggest higher infection in the age group 30–39 years followed by 20–29 years of age [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…During the initial phase of the pandemic, each country adopted various responses to COVID-19 to slow transmission and to prevent oversaturation of the healthcare systems (6)(7)(8)(9). Bhutan adopted proactive prevention methods to limit community transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the promising results, the analysis considered here has few limitations. This analysis uses data that is different from the true data on the ground due to less testing and inefficient counting of new and death cases by Nepal and India (43)(44)(45)(46). Similarly, multivariate distance correlation can be used to determine the dependencies by including other factors of transmission and vaccination rate.…”
Section: Discussionmentioning
confidence: 99%